Effectiveness of concussion treatments in older adults: a systematic review protocol - Lindsey Sikora; Roger Zemek; Chantal Backman; Sharon Johnston; Peter Tanuseputro; Stacey Fisher; Wenshan Li; Stephen G Fung; Franciely Daiana Engel; Aurelie Tonjock Fonka; Rosie Papp; Ashley Lam (BMJ Open)
Introduction Concussions can have significant implications on the health and quality of life of older adults. As most concussion research previously focused on children, athletes and military populations, there is a need to better understand the concussion-specific treatments for adults aged 65 and older. The aim of our systematic review is to review the existing literature on the effectiveness of concussion treatments on outcomes in adults aged 65 and older.Methods and analysis This systematic review will be conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines and the Cochrane’s Handbook for Systematic Reviews of Interventions. A comprehensive search of electronic databases (MEDLINE, Embase, CINAHL, AgeLine, APA PsycNet and Cochrane CENTRAL) will be performed and reference lists of included articles will be searched. We will conduct a two-step screening process and data extraction. The data analysis will integrate a narrative approach with vote-counting. The risk of bias in the included studies will be assessed, and the quality of evidence for each outcome will be evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach.Ethics and dissemination The results of this systematic review will contribute to the current knowledge on concussion treatments and outcomes in older adults. This work is essential for identifying effective interventions and guiding future guidelines for this under-represented population. No ethical approval is needed for the review, and we plan to present the results at an international research conference and in a peer-reviewed journal. This protocol is registered in PROSPERO (CRD # pending).